KAJIAN PENERAPAN SI / TI DALAM MENINGKATKAN KUALITAS PEMBELAJARAN PADA TRAINING CENTER DENGAN MENGGUNAKAN METODOLOGI DeLone And McLean : STUDI KASUS PADA BINUS CENTER JAKARTA - Nyoman Ayu Gita Gayatri; GG Faniru Pakuning Desak (Universitas Muhammadiyah Tangerang, 2017)
The development of information technology has given the world an influence on education, especially in learning. The role of information technology and information systems in the field of informal education and one of them can be seen in the use of instructional media in the learning space, the utilization of classrooms and academic information system that can facilitate the conduct implementation of academic activities. Binus Center Jakarta is one of the providers of informal education, especially education. Binus Center using information technology in improving quality of learning, there are three things that must be realized that (1) Participants and the instructor must have access to digital technology and the Internet in classrooms (2) Available materials quality and meaningful, and (3) Instructors must have knowledge and skills in using the tools and digital resources to help participants to achieve quality learning. This study aimed to see whether the implementation of information systems / information technology (IS / IT) affects the quality of learning in non-formal education, using case studies on Jakarta Binus Center Special Class program in particular. This study uses qualitative research methodology with inferential statistical analysis to describe correlation of information systems implementation to quality learning. Keywords: Implementation of IT / SI, Quality Learning.